Taxation and Capital Structure : Evidence from a Transition Economy - Klapper, Leora; Tzioumis, Konstantinos (World Bank, Washington, DC, 2012)
The authors examine the effects of taxation on financing policy using the corporate tax reform in 2001 in Croatia as a natural experiment. Since the extant literature on tax effects on capital structure studies listed firms in developed countries, it is worth investigating whether the same results apply to privately-held, small and medium size firms in transition economies. The findings provide significant evidence that lower taxes have affected the capital structure of Croatian firms, resulting in increased equity levels and decreased long-term debt levels. The authors also find that smaller and more profitable firms were more likely to reduce their debt levels. These findings are consistent with the trade-off theory of capital structure, which suggests that lower taxes decrease the incentive to hold debt due to decreasing interest tax deductibility.